Analisis Kemampuan Berfikir Inventif Siswa pada Pembelajaran Daring di SMP Negeri 5 Kecamatan Ukui - Radeswandri Radeswandri; Indria Kirana; Richa Dwi Rahmawati (Milenial: Journal for Teachers and Learning, 2022)
To face challenges in the 21st century efficiently and effectively, a country needs students who have inventive thinking in addition to being innovative and creative. The low level of student mindset is an obstacle in the current global era. Therefore, this study aims to analyze students' inventive thinking skills in online learning at SMP Negeri 5 Ukui sub-district. The research method used is a survey method. The database of students' creative thinking abilities was collected through online questionnaires/questionnaires using Google Form, then analyzed descriptively using the SPSS version 23.00 program for Windows. The subjects used as research samples were 55 students of class IX SMP Negeri 5 Ukui. The results showed that the mastery of the elements of students' inventive thinking skills at SMP Negeri 5 Ukui had an average of 3.81 in the Good category. Obtaining the good category, seen from the respondents' responses, namely students have a high curiosity very well. Based on the results and discussion, it can be concluded that the inventive thinking ability of students with a total frequency of 55 students, overall shows that students of SMP Negeri 5 Ukui have good inventive thinking skills, where an average of 3.81 or 10 is also shown by the results of the category. in good presentation. From this research, it is hoped that students' inventive thinking skills will continue to develop both from flexibility and complexity, self-regulation, curiosity, creativity, being able to take risks and high-level thinking.